Analysis of Syntactical Stylistic Devices on Poems in Hello Magazine - Rini Safitri; Rusdi Noor Rosa (English Language and Literature, 2018)
This paper aims at describing syntactical stylistic devices used in the poems published in Hello magazine. This study was conducted using a content analysis method. Five editions of Hello magazine published from February 2010 to December 2010 were taken as the source of data. Based on the data analysis, the poems in Hello magazine use seven types of syntactical stylistic devices, they are inversion, parallelism, climax, repetition, asyndenton, rhetorical question, and question in narrative. The syntactical stylistic device mostly used by the writers of the poems published in Hello magazine is parallelism and the least frequent devices used are climax and question in narrative. By using parallelism in poems, the writer is able to catch reader’s attention to focus on the content of the poem.